Efficacy of CAD/CAM Technology in Interventions Implemented in Orthodontics: A Scoping Review of Clinical Trials. (2nd June 2022) - Ardila, Carlos M.; Elorza-Durán, Andrés; Arrubla-Escobar, Daniel
Abstract : Objectives . To evaluate the efficacy of computer-aided design/computer-aided manufacturing (CAD/CAM) technology in interventions implemented in orthodontics. Methods . A scoping review of scientific evidence was accomplished, involving different databases. MesH terms and keywords were provided to examine clinical trials (CTs) in all languages. Exclusively CTs that fulfilled the eligibility criteria were admitted. Results . Eight CTs were chosen. These experiments evaluated 542 patients. Four CTs compared the computer-aided indirect bonding method versus the traditional direct bonding of orthodontic brackets. Three CTs compared CAD/CAM retainers with other types of retainers, and one CT compared the CAD/CAM group with multistranded stainless steel wires versus stainless steel wires. Regarding the efficacy of the interventions with CAD/CAM technology used in orthodontics, variable results were found. The indirect bonded customized CAD/CAM brackets presented just a slight effect on the treatment efficacy and therapy results. Two CTs showed that an indirect bonding self-ligating standard system had a similar quality of therapy in comparison with the CAD/CAM customized bracket system. Concerning the clinical failure rate, no differences were presented between the CAD/CAM retainer and other retainers. A CAD/CAM system had more loose brackets than a noncustomized system and was observed also a greater amount of immediate debonding with CAD/CAM indirect bonding than with direct bonding. CAD/CAM fixed retainers revealed inferior relapse and fewer failures than lab-based and conventional chairside retainers. No changes between treatment groups were observed regarding the total therapy time, amount of appointments, and quantity of archwire bends. Conclusions . In general terms, no greater efficacy of CAD/CAM technology was observed over traditional therapies used in orthodontics. However, it was found that gingival inflammation and the accumulation of bacterial plaque and dental calculus were lower when CAD/CAM retainers were used. When comparing interventions that include CAD/CAM systems with conventional therapies, no significant reduction in care times was found.